OPTIMASI TOPOLOGI PADA CHASSIS KENDARAAN BIO-HYBRID (OBHI-MEC UNUD) DENGAN MENGGUNAKAN ANSYS WORKBENCH - Darmawan, William Halim; Karohika, I Made Gatot; Widiyarta, I Made (Teknik Desain Mekanika, 2024)
Abstract The chassis or main frame is the basic structure of the vehicle to which other components are attached. In this study, the Obhimec vehicle chassis will be topology optimized using mass variations. There are 3 mass variations used, namely, 20%, 25% and 29%. Simulations on the Ohbi-mec chassis before optimization with a mass of 155.37 Kg get the results of von mises stress 22.988 Mpa and safety factor 8.7004. Simulations with the best results in the 29% reduction variation with a mass of 110.68 Kg get the results of total deformation 0.18574, von mises stress 44.966 Mpa, strain 0.00021218 and safety factor 4.4478. Keywords: Topology Optimization, Ansys Workbench, Chassis, Ohbi-mec.